Design of internal non-circular gear- train with improved cycloid profile - Nguyen Hoang Viet; Nguyen Thuy Duong; Nguyen Thanh Trung; Nguyen Hong Thai (Journal of Technical Education Science, 2020)
An improved cycloid is formed from a fixed point on an ellipse when it rolls without slipping on the pitch circle gear, which is proposed for the rotor design of a Lobe pump in recent years. Hitherto, there have been no works using this curve to design the tooth profile of a non-circular gear. This paper presents the method to design a pair of non-circular gears using the improved cycloid as the tooth profile to create a variable gear ratio function. The authors also set up this tooth profile for an eccentric circular gear. On this basis, the tooth profile of the mating non-circular gear with the eccentric circular gear is shaped based on the meshing condition of the gearing theory to form internal non-circular gears.